Study of land cover of Monte Forgoselo using Landsat Thematic Mapper 5 images (Galicia, NW Spain) (2015)
The aim of this study was to carry out a land cover classification of Monte Forgoselo. Remote sensing as a planning tool has been used, specifically, a satellite image Landsat 5. We perform a supervised digital classification of the maximum likelihood, minimum distance and parallelepipeds. The result has been the division of Monte Forgoselo into categories of types of vegetation, particularly in pine forest, scrub and grassland, reaching a Kappa coefficient of 0.9762 and an overall accuracy of 98.3586%, which means good reliability. In addition, we found that the use of such techniques can get to make a planing of this small rural area, focusing on forestry management. Furthermore, the use of remote sensing is considered viable in the performance of work with more consideration.